The Influence of Celebrity Endorsement and The Advertisement Message Towards Telkomsel's Product Awareness and Its Impact on The Purchase Intention - Ayuni, Dinda Mutiara; Prasetyawati, Yuliana Riana (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2020)
The phenomenon of increasing number of data services usage in Indonesia has triggered each operator (telecommunication companies) to have an actual tariff war related to the demands. Contradicted to those phenomena, Telkomsel, resisted to compete in the lower prices. Instead, using Raffi Ahmad as the endorser for their latest internet package, which is expected to fit the role to influencing the upper-class prospective customers. This study aims to determine the influence of Celebrity Endorsement and Advertisement Message to Purchase Intention through Telkomsel’s Product Awareness. This study is using non-probability sampling techniques with purposive sampling approach, with the sample of 205 respondents that have seen Telkomsel’s OMG product advertising on digital media. The methodology of this research is quantitative approach and the data obtained are tested using path analysis model. Both Celebrity Endorsement and Advertisement Message have a significance influence towards Product Awareness and Purchase Intention partially. The result also shows that there is a higher indirect influence among Celebrity Endorsement to Purchase Intention and Advertising Message to Purchase Intention by 0.3759 and 0.4716 respectively.